Electrochemical oxidation of carbon fibres: adsorption of the electrolyte and its effect on interfacial adhesion - SZAZDI, Laszlo; GULYAS, Janos; PUKANSZKY, Béla (Composites. Part A, Applied science and manufacturing, 2002)
A preliminary study indicated the adsorption of sodium hydroxide electrolyte to carbon fibre oxidised in a continuous anodic electrochemical process. The adhesion of the oxidised fibres to epoxy resin decreased with increasing amount of adsorbed NaOH. In this study, experiments were carried out to confirm the preliminary observations. Bundles of fibres were soaked in water and both the solution and the fibre were analysed. The results proved that sodium hydroxide is removed slowly from the fibre surface, more than 20 h is needed to create a relatively clean surface. The adsorbed NaOH blocks reactive groups and hinders coupling between the matrix and the fibre. Its removal increases both the chemical and the electrochemical activity of the fibre and leads to a significant improvement of interfacial adhesion.